ATOMS: ALMA three-millimeter observations of massive star-forming regions – III. Catalogues of candidate hot molecular cores and hyper/ultra compact H ii regions. Issue 2 (17th May 2021) - Liu, Hong-Li; Liu, Tie; Evans II, Neal J; Wang, Ke; Garay, Guido; Qin, Sheng-Li; Li, Shanghuo; Stutz, Amelia; Goldsmith, Paul F; Liu, Sheng-Yuan; Tej, Anandmayee; Zhang, Qizhou; et al.
ABSTRACT: We have identified 453 compact dense cores in 3 mm continuum emission maps in the ALMA Three-millimetre Observations of Massive Star-forming regions survey, and compiled three catalogues of high-mass star-forming cores. One catalogue, referred to as hyper/ultra compact (H/UC)-H ii catalogue, includes 89 cores that enshroud H/UC H ii regions as characterized by associated compact H40α emission. A second catalogue, referred to as pure s-cHMC, includes 32 candidate hot molecular cores (HMCs) showing rich spectra ( N ≥ 20 lines) of complex organic molecules (COMs) and not associated with H/UC-H ii regions. The third catalogue, referred to as pure w-cHMC, includes 58 candidate HMCs with relatively low levels of COM richness and not associated with H/UC-H ii regions. These three catalogues of dense cores provide an important foundation for future studies of the early stages of high-mass star formation across the Milky Way. We also find that nearly half of H/UC-H ii cores are candidate HMCs. From the number counts of COM-containing and H/UC-H ii cores, we suggest that the duration of high-mass protostellar cores showing chemically rich features is at least comparable to the lifetime of H/UC-H ii regions. For cores in the H/UC-H ii catalogue, the width of the H40α line increases as the core size decreases, suggesting that the non-thermal dynamical and/or pressure line-broadening mechanisms dominate on the smaller scales of the H/UC-H ii cores.